ChemInform Abstract: Platinum Carbonyl Clusters Chemistry: Four Decades of Challenging Nanoscience. Issue 12 (25th March 2014) - Ciabatti, Iacopo; Femoni, Cristina; Iapalucci, Maria Carmela; Longoni, Giuliano; Zacchini, Stefano
Abstract Review: 117 refs.